Analysis of Anorexia Nervosa Reflected in Marti Noxon’s To The Bone (2017) - Rahayuningsih; Latifah Dwi Ariyani (Metaphor, 2026)
This study aims to analyze: (1) Anorexia Nervosa symptoms reflected in Marti Noxon’s To the Bone (2017), (2) the mental condition of the main character who suffers from Anorexia Nervosa in Marti Noxon’s To the Bone (2017). The study uses a qualitative method to analyze the film entitled To the Bone, directed by Marti Noxon, as the objective research. The collecting data of the research method includes watching, identifying, classifying, and selecting. The analyzing data of the research method involves displaying, explaining, and interpreting. The researcher analyzes the data by using Sigmund Freud's theory of Personality. The result of the study: (1) the representation of Anorexia Nervosa’s symptoms in Marti Noxon’s To the Bone (2017), including id-driven symptoms in Ellen, ego and defensive mechanism, and superego and moral pressure, (2) the mental condition of the main character who suffers from Anorexia Nervosa, including internal conflict between id, ego, and superego, identity crisis, and possibility of recovery.